Platelet Counts and Indices Are Altered in Pre-Eclampsia - Saini, Vandana; Vallepu, Vijaya; Gupta, Mamta (Annals of Pathology and Laboratory Medicine, 2020)
BACKGROUND: Endothelial damage and activation of platelets leading to their increased consumption and increase in production of young platelets by bone marrow is the most common pathophysiology of pre-eclampsia. Thus, fall in platelet count and altered platelet indices may have diagnostic as well as prognostic value in pre-eclampsia. AIM: To evaluate platelet count and platelet indices between pre-eclamptic and normotensive women and to assess their association with severity of pre-eclampsia. METHODS: Platelet counts and indices were estimated in 30 normotensive and 30 PE women at 20-24 weeks pregnancy and were repeated after every 4 weeks. RESULTS: Mean platelet counts, platelet volume, platelet distribution width, and platelet large cell ratio between pre-eclampsia and normotensive women were significantly altered in PE women and were associated with severity of PE. This alteration of platelet count and indices occurred even before the rise of BP. CONCLUSION: All the platelet indices were found to be reliable markers of PE and were found to be increased much earlier than BP. MPV had the maximum sensitivity (96.7%) and specificity (93.3%) and was the most reliable biomarker.